Penerapan Sustainable Design Terhadap Material Interior Pada Green Village di Bali (Garden Villa) - Kim Febriany; mariana wibowo; dody wondo (Intra, 2013)
Garden Villa is one of the base units in Green Village, Bali in Taman Ayu Sibanggede Abiansemal street close to the Ayung river which is one of the major rivers in Bali. According to the designers of the group Green Village designer Ibuku, Garden Villa has a concept of Sustainable Design in the furniture and interior materials. Sustainable Design is a design which is during the process of taking the resources that exist in nature until reprocessing using methods that are not harmful to the environment or human health, so that the life of man and nature in the earth can continue to survive. Used to assess these data processing methods such as field observations, interviews, documentation, literature, and questionnaires. Then also use a mix of data analysis methods. Results from this study is the first, the material on the interior Garden Villa did not fully implement the Sustainable Design by comparing it with the principles of Sustainable Design, the operational principles, philosophy, and practice. Interior materials at Garden Villa meet operational principles by working with parties related to sustainable design decisions on the PT. Bamboopure Bali, Indonesia, the principle of philosophy that uses natural resources such as renewable and recyclable bamboo such as glass, stone, brass, and fabric, then the material is easy care, and practice the principles which were given coating material and preserved beforehand (bamboo) so it can be more durable. Does not meet the principles of philosophy because most of the bamboo used from Java so that no energy efficiency, and principles of practice due to one of the aspects of material processing such as finishing, and adhesive because it contains a substance does not meet the VOC (Volatile Organic Compound) Second, the questionnaire method used to determine whether the residence with the concept of Sustainable Design comfortable place to live or not. Number of respondents by 25 people who are residents of Green Village outcome is overall 90% felt comfortable staying at Green Village in Bali because of the atmosphere, facilities, and hygiene at Villa.